Expression of six3 and otx in Solenogastres (Mollusca) supports an ancestral role in bilaterian anterior‐posterior axis patterning. Issue 1 (15th December 2017) - Redl, Emanuel; Scherholz, Maik; Wollesen, Tim; Todt, Christiane; Wanninger, Andreas
Abstract : The homeodomain transcription factors six3 and otx are involved in patterning the anterior body and parts of the central nervous system (CNS) in bilaterians. Their similar expression patterns have been used as an argument for homology of heads, brains, segmentation, and ciliated larvae. We investigated the developmental expression of six3 and otx in the aplacophoran mollusk Wirenia argentea . Six3 is expressed in subepithelial cells delimiting the apical organ of the solenogaster pericalymma larva. Otx is expressed in cells of the prototroch and adjacent regions as well as in posterior extensions of the prototrochal expression domain. Advanced larvae also show pretrochal otx expression in the developing CNS. Comparative analysis of six3 and otx expression in bilaterians argues for an ancestral function in anterior‐posterior body axis patterning but, due to its presence in animals lacking a head and/or a brain, not necessarily for the presence of these morphological structures in the last common ancestor (LCA) of bilaterians. Likewise, the hypothesis that the posterior border of otx expression corresponds to the border between the unsegmented head and the segmented trunk of the LCA of protostomes is not supported, since otx is extensively expressed in the trunk in W. argentea and numerous other protostomes.